Tantangan Etika dan Tanggung Jawab Robotics Engineer Dalam Pengembangan Robot Barista Berbasis IoT - Muhammad Sulthonul Izza; Intan Permata Sari Fauziah; Sekar Tri Handayani; Farrel Athaillah Putra; Fittra Marga Ardana; Florentina Yuni Arini (Jurnal Ilmiah Informatika Global, 2025)
Over the past few decades, technology has advanced at a tremendous pace, especially related to social robotics based on the Internet of Things has significantly influenced many aspects of human life. A concrete example of its application is a robot barista designed to interact and collaborate with humans, creating a new relationship between humans and machines. However, the presence of these robots also poses ethical challenges and professional responsibilities, especially regarding data privacy, security, and social impact. This research seeks to determine and assess the primary challenges robotics engineers face in designing safe and ethical robotics systems. Through a literature study approach that includes collecting, reviewing, and analyzing various relevant scientific sources related to ethical issues in robotics and IoT technology, it was found that robotics engineers must consider aspects of security and personal data protection as well as potential social impacts such as inequality and employment reduction. This research emphasizes the importance of ethics education and the establishment of high professional standards in addition to the need for clear ethical guidelines through cross-sector collaboration. Thus, the development of IoT-based barista robots is expected to not only drive technological progress, but also bring sustainable and responsible benefits to society.